Molluscs - Diarte-Plata, Genaro; Escamilla-Montes, Ruth (IntechOpen, 2019)
This book is divided into four sections. The first section "Introduction" offers information on mollusc generalities. In addition, these organisms are important in areas of commercial significance such as aquaculture and fishing. Similarly, it was pointed out in the use of molluscs have uses in pollution studies and environmental processes among others. The second section "Social Aspects of Fisheries" considers aspects of molluscs gathering in tropical regions. The third section "Ecology" presents the results of long-term research concerning the study of variability of the size/mass relationships in the mollusc Rapana venosa from the northwestern part of the Black Sea and near the eastern coast of Crimea (Sudak Gulf). The fourth section "Immune System" sheds light on the elements of the molluscan immune system and survival differences against Vibrio vulnificus and Vibrio parahaemolyticus. This book can be consulted by students, professors, and researchers in biological sciences and related areas.